2004
DOI: 10.1159/000078215
|View full text |Cite
|
Sign up to set email alerts
|

Long dsRNA and silent genes strike back:RNAi in mouse oocytes and early embryos

Abstract: RNA interference (RNAi) refers to the selective degradation of mRNA induced by double-stranded RNA (dsRNA), first discovered in Caenorhabditis elegans. Homology-dependent silencing phenomena related to RNAi have been observed in many species from all eukaryotic kingdoms. RNAi and related mechanisms share several conserved components. The hallmark of these phenomena is the presence of short dsRNA molecules (21–25 bp long), termed short interfering RNA (siRNA), which are generated from dsRNA by the activity of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 97 publications
(157 reference statements)
1
22
0
Order By: Relevance
“…Therefore, variation in developmental capacity due to the microinjection procedure has been ruled out. Previous studies have shown that the mechanism of RNAi is limited at the post-transcriptional level by degrading the sequence-specific mRNA or blocking the activity of ribosomal RNA (rRNA) (Svoboda 2004), which leads to a loss of function in mice (Svoboda et al 2000, Wianny & Zernicka-Goetz 2000, Grabarek et al 2002, Siddall et al 2002. Our results also showed that the injection of dsRNA of oocyte-or zygote-specific transcripts induced sequence-specific mRNA degradation and prevented subsequent protein synthesis during development of preimplantation embryos.…”
Section: Discussionsupporting
confidence: 66%
“…Therefore, variation in developmental capacity due to the microinjection procedure has been ruled out. Previous studies have shown that the mechanism of RNAi is limited at the post-transcriptional level by degrading the sequence-specific mRNA or blocking the activity of ribosomal RNA (rRNA) (Svoboda 2004), which leads to a loss of function in mice (Svoboda et al 2000, Wianny & Zernicka-Goetz 2000, Grabarek et al 2002, Siddall et al 2002. Our results also showed that the injection of dsRNA of oocyte-or zygote-specific transcripts induced sequence-specific mRNA degradation and prevented subsequent protein synthesis during development of preimplantation embryos.…”
Section: Discussionsupporting
confidence: 66%
“…However, this replacement was not equivalent to LGN reduction or depletion because LGN-N-GFP functions similarly to LGN at the spindle and endogenous LGN is still functional whether it is localized to the spindle or not, making the overexpression effect of LGN-N-GFP similar to that of LGN. Double-stranded RNA-mediated mRNA degradation is an effective approach to knock down a gene in mouse oocytes without inducing an apoptotic response [23,24,34]. Using this technique, we reduced the maternally stored LGN mRNA by more than 90% by 40 h. Although LGN protein has a low turnover rate and was only reduced by about 50%, dsRNA-mediated downregulation of LGN revealed its roles in meiotic spindle organization.…”
Section: Discussionmentioning
confidence: 99%
“…Today, long RNA hairpins are shadowed by short hairpin systems, and they are used only in special cases where a short hairpin RNA system cannot be used efficiently. Long hairpin RNA was successfully used to block gene function in several types of mammalian cells, but aside from mouse oocytes, it never acquired wider attention (reviewed in [139]). Long dsRNA expression from a large inverted repeat remains a common solution for transgenic RNAi approach in invertebrates and plants.…”
Section: Do Long Hairpin Rnas Naturally Occur In Mammals?mentioning
confidence: 99%
“…It can also be combined with tissue-specific pol II promoters. Working with inverted repeats may be complicated (reviewed in [139]), but despite all the possible pitfalls, transgenic RNAi in mouse oocytes has produced a functional knockdown in several instances [120,[140][141][142], and the list of successful knockdowns in Caenorhabditis and Drosophila is much longer.…”
Section: Do Long Hairpin Rnas Naturally Occur In Mammals?mentioning
confidence: 99%